2003
DOI: 10.1007/s00268-002-6279-7
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Factors Associated with Recurrence Patterns after Intended Curative Surgery for Gastric Cancer

Abstract: Recurrence after curative resection for gastric cancer remains high. We examined its incidence and factors related to recurrence pattern, while trying to avoid the interaction of various factors. A total of 611 gastric cancer patients after resection for curative intent (1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995) were analyzed. The result showed that 245 patients had recurrence (40.1%). Cumulative recurrence rates were 53.5%,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(81 citation statements)
references
References 31 publications
(49 reference statements)
5
71
0
5
Order By: Relevance
“…In a study by Wu et al . (11), cumulative recurrence rates were 53.5%, 80.0%, 89.0%, 94.7%, 96.3%, 98.0%, and 99.5% at 1, 2, 3, 4, 5, 6, and 7 years, respectively. Lee et al .…”
Section: Discussionmentioning
confidence: 88%
“…In a study by Wu et al . (11), cumulative recurrence rates were 53.5%, 80.0%, 89.0%, 94.7%, 96.3%, 98.0%, and 99.5% at 1, 2, 3, 4, 5, 6, and 7 years, respectively. Lee et al .…”
Section: Discussionmentioning
confidence: 88%
“…The incidence of distant metastasis was comparably high (30–45%) all over the world [3, 5, 7, 8, 1012, 17, 18]. Patients in Japan and South Korea suffered lower local-regional recurrence compared with China (7-10 vs. 32.4%) [79].…”
Section: Discussionmentioning
confidence: 99%
“…Locoregional recurrence occurs most commonly at the anastomosis site or stump [6]. An isolated locoregional recurrence was reported in 6% to 46% of patients who underwent surgical resection [4,6,9,11,12]. Locoregional recurrence results from direct tumor proliferation or lymphatic spread within the abdominal cavity [13].…”
Section: Discussionmentioning
confidence: 99%
“…More than 90% of patients relapse within five years after surgery, and 70% relapse within two years. Wu et al [4] reported that cumulative recurrence rates were 53.5%, 80.0%, 89.0%, 94.7%, and 96.3% at 1, 2, 3, 4, and 5 years, respectively. These high rates of recurrence have been attributed to abundant lymphatic channels within the gastric wall that provide channels for mucosal skip lesions and numerous potential pathways of lymphatic drainage away from the stomach.…”
Section: Introductionmentioning
confidence: 99%